As Relações Portugal-Brasil e a emigração portuguesa. O impacto da legislação nacionalista de Getúlio Vargas - Paula Marques Santos; Diogo Ferreira (História - Revista da Faculdade de Letras da Universidade do Porto, 2017)
During the 1930s and 1940s Portugal and Brazil had simultaneously Estado Novo regimes. The Portuguese regime had however a longer duration. During this period, the relationship between Portugal and Brazil will be influenced by international affairs and by political, diplomatic and legislative options followed by national governments. With this article, we wish to try to understand the international situation’s framework, that influences each of the countries and regimes and to point out how the political options influenced the migratory movements between the two sides of the Atlantic. For this, we will go through some of Getúlio Vargas' Estado Novo legislation, in order to try to stress the efforts made by Portugal, in maintaining a close relationship between the two regimes